Application of Heated Water to Reduce Populations of Brettanomyces bruxellensis Present in Oak Barrel Staves - Edwards, C.G.; Cartwright, Z.M. (South African Journal of Enology and Viticulture, 2018)
New 16 L and three-year-old commercial 225 L barrels representing French and American oaks of different toasting levels, contaminated with Brettanomyces bruxellensis, were obtained. Center sections of individual staves were sawn into 3 x 3 cm cubes and submerged 2 mm into heated water at 50°C, 60°C, 70°C, or 80°C. Following heat treatment, cross sections and/or shavings were collected and transferred into a yeast recovery medium for incubation for ≥60 days. Culturable cells were not recovered from cubes heated in water at 70°C for 20 minutes, or 80°C for 15 minutes, when the yeast was present in oak at depths of ≤4 mm. However, longer heating times (70°C for 30 min or 80°C for 20 min) were required if B. bruxellensis was present at depths of 5 to 9 mm within cubes made from staves. Based on these results, heating water to at least 70°C for a minimum of 30 minutes is recommended to reduce risk of wine spoilage by barrels contaminated with B. bruxellensis.